*Elementos del erotismo en varios cuentos de Andrés Caicedo - Carvajal, Edwin Alberto (Íkala, Revista de Lenguaje y Cultura, 2000)
In his collection of short stories entitled Calilabazo, Colombian writerAndrés Caicedo presents love and eroticism as feelings which find almost no way to reveal themselves other than physically. Thus it is through their gaze, their voice and their body that the main characters and the narrator convey their thoughts and actions. And out of these it is the the body which is the prime scenario of the main characters'eroticism, violence, perversion and the fight for survival, be they transgressors or victims. How to reference this article: Carvajal, E. A. (2000). Elementos del erotismo en varios cuentos de Andrés Caicedo. Íkala. 5 (1-2), pp. 143 – 158